Directional sensing based on flexible aligned carbon nanotube film nanocomposites. Issue 31 (26th July 2018) - Sui, Chao; Yang, Yingchao; Headrick, Robert J.; Pan, Zixuan; Wu, Jianyang; Zhang, Jing; Jia, Shuai; Li, Xinwei; Gao, Weilu; Dewey, Oliver S.; Wang, Chao; He, Xiaodong; et al.
Abstract : An aligned SWCNT-film with anisotropic mechanical and electrical properties was utilized to prepare directional sensor. Abstract : The electrical behaviors under mechanical deformation of an aligned single-walled carbon nanotube (SWCNT) film nanocomposite have been systematically investigated in this work. Electrical signals along the CNT axis (‖) and perpendicular to the CNT axis (⊥) follow a specific pattern, which enables the mechanical motion to be determined by vector analysis of such signals. The unique electrical behaviors of the sandwiched nanocomposites originate from the anisotropic characteristics of the CNT films. By combining in situ mechanical investigation with a coarse-grained molecular dynamics simulation, the shearing effect between SWCNTs is found to play a key role in stress-transfer along the ‖ direction, resulting in arc-shape cracks, while the peeling effect is dominant along the ⊥ direction, leading to unifom SWCNT bar bridging at cracks. The fabricated CNT based sandwiched nanocomposite is believed to have great potential in building flexible all-direction sensors.